Security Mandated Analytics based Route Processing with Digital Signature [SMARPDS] - Pseudonymous Mobile Ad Hoc Routing Protocol - K. Vinayakan; M. V. Srinath (Institute of Advanced Engineering and Science, 2018)
There are a lot of speculations going on about the interests for privacy in mobile network. Many research works have been proposed in the aspect and these works concentrate more on the anonymity part and there are quite a few implementations of these research works on some applications. Ad hoc routing protocols must have provision for both anonymity providing nature and restriction of information collection from unauthorized nodes. Till recent times, there are a number of ad hoc routing protocols that have been introduced. But, they have lack security features or authentication features or in some cases both. The lack of proper security features leads to a state of vulnerability which at any given point, will act as a threat element. In this paper, we propose Security Mandated Analytics based Route Processing with Digital Signature protocol [SMARPDS]. It is an anonymous and authentication providing routing protocol in Mobile Ad hoc network. In addition, routes are discovered based on analytics done on the node and its present location in the network. SMARPDS provides authentication during the route discovery and transmission process by employing digital signatures on node front and also on packets front.